Clinical profile and outcomes of snake bite poisoning in a tertiary care centre in South Tamilnadu - B., Meenakshi; K., Shantaraman; M., Indhumathi; Mohan, Arumugapandian S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Snake-bites are well-known common medical emergencies in many parts of the world. In India 46,000 people are dying every year from snakebites. However, the true scale of mortality and morbidity from snake-bite remains uncertain. This study analyses the clinical profile and outcomes of the snake bite poisoning in patients admitted to this centre. Methods: This cross sectional study analyses the data of 150patients admitted to the Intensive Medical Care Unit of Tirunelveli Medical College Hospital with the history of snake bite between April and September of 2015 as available in their case records. Results: In this study, 42.7% of the patients were in the age group of 18 to 40 years and 64% were males with rural: urban ratio of 2.3: 1. About 82.7% of bites were haematotoxic, 10.7% neurotoxic and the remaining nontoxic bites. About 54% patients recovered completely, 44% had some form of morbidity at discharge and mortality was 2%. Out of 136 patients who were treated with Anti-snake venom (ASV), 9.6% developed ADR. The common ADR was itching and hypotension followed by rigor, breathlessness and edema of lips and eyes. Conclusions: This study highlights the need for early treatment intervention post bite. Imparting health education about early pre-hospital management and transfer to the hospital will help in the prevention of deaths due to snakebite. Identification of the type of snake is essential to decide on the type of toxicity and method of treatment to be instituted.